The Cytosolic Domain of Bcl-2 Oligomerizes to Form Pores in Model Mitochondrial Outer Membrane at Acidic pH - Peng, Jun (2009)
The three dimensional structures of both pro-apoptotic Bax and anti-apoptotic Bcl-2 are strikingly similar to that of pore-forming domains of diphtheria toxin and E. coli colicins. Consistent with the structural similarity, both Bax and Bcl-2 have been shown to possess pore-forming property in the membrane. However, these pore-forming proteins use different mechanisms to form pores. While Bax and diphtheria toxin form pores via oligomerization, the colicin pore is formed only by colicin monomers. Although oligomers of Bcl-2 proteins have been found in the mitochondria of both healthy and apoptotic cells, it is unknown whether or not oligomerization is involved in its pore formation. To determine the mechanism of Bcl-2 pore formation, we reconstituted the pore-forming process of Bcl-2 using purified proteins and liposomes. We found that Bcl-2 pore size depended on Bcl-2 concentration; and smaller entrapped molecules released faster than larger ones from liposomes at a given Bcl-2 concentration. Moreover, the rate of dye release mediated by pre-formed wild-type Bcl-2 oligomers or by the mutant Bcl-2 monomers with a higher homo-association affinity was much higher than that by wild-type Bcl-2 monomers. Together, it is suggested that oligomerization is likely involved in Bcl-2 pore formation.